Modeling of the elementary properties of a language system through the prism of the theory on the systems organization - D. M. Mironova (Гуманитарные и юридические исследования)
The research is prepared in line with the system studies of language, designed to characterize it from the point of view of the most important characteristics of system ontology. The relevance of such studies in contemporary linguistics is caused to the insufficient development of the system model of language, taking into account the anthropocentric functions of this phenomenon. Research attention is focused on some of the most important aspects of the organization of the language system, as they are presented in relation to its function – to be a means of acquiring, processing, storing and revealing the content of consciousness. This subject of consideration determines the novelty of the research, as well as the methodology corresponding to this subject. The research put forward as the leading method the method of systemological interpretation of language / speech phenomena caused by the tasks of verbal conceptualization or categorization of real objects. Based on complex approach that combines the attitudes of systems theory and cognitive linguistics, the author makes an analysis of the elementary qualities of natural language, which mean the properties of its compound. The cognitively directed organization of the components of a language system is considered in relation to such universal principles of the organization of system objects as the presence of substantial limitations in the system, the dependence of goal formation on external and internal factors, mutual double regulation, the relativity of the exposure on the environment, specialization, coordination and selection of the most effective components. With the use of particular linguistic phenomena from the field of sign units the research illustrates the implementation of the laws of formation and regulation of systemic organization, contributing to the language conceptualization of the world.